2016
DOI: 10.1108/hff-09-2014-0281
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of transient forced convection in a square enclosure containing two heated circular cylinders

Abstract: The present work is aimed to study unsteady forced convection of two heated horizontal cylinders confined in a 2-D square enclosure. The widths of the inlet and outlet ports are equal to 10% of the enclosure height. The cylinders are located at the middle of the enclosure height and the walls of the cavity are adiabatic. The simulations are carried out for Reynolds numbers between 380 and 550 and dimensionless horizontal distances of cylinders at 0.1, 0.2 and 0.3, respectively. The results indicate that the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The results show how the magnetic field affects the thermal behavior of the system. Talkhoncheh et al (2016) included the impact of time on thermal activity of hot bodies inside a ventilated room. The results showed that there is an effect of time when the velocity of the fluid entering the chamber is very high.…”
Section: Introductionmentioning
confidence: 99%
“…The results show how the magnetic field affects the thermal behavior of the system. Talkhoncheh et al (2016) included the impact of time on thermal activity of hot bodies inside a ventilated room. The results showed that there is an effect of time when the velocity of the fluid entering the chamber is very high.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical analysis of transport phenomena in a fluid medium and thermal flows around these cylinders may provide vibrant information about mechanical quantities such as drag coefficient, recirculation zones, steady vortex, Nusselt number, and so on, which will enhance the system design and new product development. Several authors 1‐10 have examined the mixed convection and flow patterns through a square cavity under a wide range of physical situations. Darzi et al 1 used a Lattice Boltzmann approach to study the numerical problem of mixed convection and thermal activity past two circular objects within the enclosure of square cavity.…”
Section: Introductionmentioning
confidence: 99%
“…The role of an external magnetic force on the mixed convection over two heated circular cylinders with identical diameter embedded inside a square cavity was numerically investigated Chatterjee and Halder 4 . Talkhoncheh et al 5 analyzed the effects of flow unsteadiness on forced convection over two circular obstacles entrenched in a square chamber. It was demonstrated that the heat transfer effectiveness is proportional to Reynolds number whenever Re < 460 and independent of the gap between the cylinders.…”
Section: Introductionmentioning
confidence: 99%
“…(Chatterjee and Halder 2014) studied the heat transfer around a two rotating circular cylinders located inside square enclosure. (Talkhoncheh et al 2016) performed in unsteady laminar regime a flow of Newtonian fluid and forced convection heat transfer around cylinders situated inside a square cavity of single inlet and outlet ports. It was found that when Re was less than 460, the effect of space between cylinders was found to be nearly negligible.…”
Section: Introductionmentioning
confidence: 99%